Endoscopic treatment of pain in chronic pancreatitis. Issue 6 (November 2018) - Moran, Robert A.; Elmunzer, B. Joseph
Abstract : Purpose of review: Pain is the most common symptom of chronic pancreatitis, having a profound effect on patients and a broad socioeconomic impact. Endoscopy is guideline recommended as first-line management for chronic pancreatitis pain in certain clinical scenarios. Herein, we provide an evidence-based review of the endoscopic treatment of pain due to chronic pancreatitis while highlighting some important confounders in the measurement of this outcome in clinical practice and research. Recent findings: Multiple recent studies have reported on the efficacy of current endoscopic therapies for chronic pancreatitis pain. Despite the high technical success rates of these procedures, pain outcomes remain disappointing. Complex mechanisms beyond ductal hypertension, such as central sensitization, visceral hypersensitivity and inflammatory neuritis account for some of the discordance observed between the rates of technical and clinical success. In addition, the sham effect is increasingly recognized as a confounder when interpreting the procedural benefit. Nevertheless, there are multiple promising innovations in the field of pancreatic endoscopy that are aimed to improve technical and clinical outcomes, but rigorous investigation is necessary to establish their role in clinical practice. Summary: Endoscopic therapy for chronic pancreatitis pain appears to be safe and effective in certain contexts and recent innovations in the field will hopefully further improve outcomes. In addition to evaluating the technical success of endotherapy in chronic pancreatitis, methodologically rigorous research focusing on patient-centered outcomes and accounting for the sham effect is necessary to advance this field.